2015
DOI: 10.1002/2015gl064899
|View full text |Cite
|
Sign up to set email alerts
|

What hindered the El Niño pattern in 2014?

Abstract: At the beginning of 2014, an El Niño event was predicted to occur in the following winter. However, the El Niño that started to develop in 2014 was hindered in the boreal summer, and only the ocean reached a weak El Niño condition. This outcome was largely attributed to a suppressed ocean‐atmosphere interaction caused by anomalous easterly winds in the eastern equatorial Pacific. These winds were related to negative sea surface temperature anomalies (SSTAs) in the southeastern subtropical Pacific (SESP). The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 43 publications
1
49
1
1
Order By: Relevance
“…Rather than a strong 2014 El Niño event occurring, as forecast, only weak warming in the key El Niño oceanic regions ( Figure 5) was observed. This forecast "bust" [112,113] caused the ENSO prediction community to critically examine the efficacy of many of the significant ocean and atmosphere system components drawn on as a source of ENSO predictability [114][115][116]. A particular challenge for ENSO based health forecasting is the so-called "spring predictability barrier" [117][118][119].…”
Section: Enso and Health Forecastingmentioning
confidence: 99%
“…Rather than a strong 2014 El Niño event occurring, as forecast, only weak warming in the key El Niño oceanic regions ( Figure 5) was observed. This forecast "bust" [112,113] caused the ENSO prediction community to critically examine the efficacy of many of the significant ocean and atmosphere system components drawn on as a source of ENSO predictability [114][115][116]. A particular challenge for ENSO based health forecasting is the so-called "spring predictability barrier" [117][118][119].…”
Section: Enso and Health Forecastingmentioning
confidence: 99%
“…Using an ocean general circulation model, Menkes et al (2014) further showed that the SST anomaly in the eastern equatorial Pacific could be significantly enhanced at the end of 2014 if the strong WWBs that occurred in 1997 (McPhaden, 1999) were added to the forcing field. In addition, the enhanced trade wind associated with the SST cooling in the southeastern Pacific (Min et al, 2015) and the easterly wind surge occurring in the middle of 2014 Hu and Fedorov, 2016) were also proposed as the reasons for the unexpectedly weak 2014 El Niño.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Min et al (2015) showed that anomalous easterly winds in the eastern equatorial Pacific, which were induced by the negative SST anomalies in the south-eastern tropical Pacific through the WES feedback, hindered the El Niño in 2014. The anomalous easterly oceanic current forced by the easterly wind anomalies zonally advected relatively low ocean temperature westward and interrupted the Bjerknes feedback.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These studies indicate that thermodynamic coupling between the atmosphere and ocean modifies ENSO variability. Recently, Min et al (2015) showed that the anomalous easterly oceanic current, which was forced by the easterly wind anomalies associated with the SPMM, hindered the El Niño in 2014. Their study focused on the oceanic dynamic responses to wind stress anomalies.…”
Section: Introductionmentioning
confidence: 99%